349 Angioleiomyoma of the Larynx Presenting as Vocal Cord Lesion: A Rare Entity. (11th January 2018) - Khafateh, Youssef; Chandran, Swapna; Alghamdi, Mohammed; Fraig, Mostafa; Alatassi, Houda
Abstract: Angioleiomyomas or vascular leiomyomas are a benign group of slow-growing tumors arising from the smooth muscle of blood vessel walls. Although rare, they are usually found within the uterus, extremities, and gastrointestinal tract. Angioleiomyoma occurs rarely in head and neck region, with lips, ears, and nose being the most involved sites, and it can present with various symptoms depending on the exact location. We report the case of a 73-year-old man who presented with severe dysphonia. Direct laryngoscopy revealed large mass involving the anterior third of left true vocal cord in the larynx. Biopsy of the lesion demonstrates benign squamous mucosa with an underlying submucosal proliferation of smooth muscle cells admixed with thickened blood vessels. Immunohistochemical stains reveal that tumor cells are positive for muscle specific actin while negative for HMB45, CK AE1/AE3, and S100. This profile is compatible with diagnosis of angioleiomyoma. In recent follow-up visit five months after laryngoscopic excision, the patient had no symptoms or signs of tumor recurrence. Fewer than 30 cases of laryngeal angioleiomyoma were reported in the literature. The tumor has male predominance and variable occurrence sites in larynx, with the supraglottic region being the most common. The main documented symptoms of reported cases are hoarseness, dyspnea, dysphagia, and foreign body sensation. There is no standardized treatment for laryngeal leiomyoma due to its rarity, but complete lesion resection is the most commonly chosen one. The choice of excision procedure between direct laryngoscopy and open neck approach is decided by tumor size, expected amount of blood loss, and any comorbidity the patient might have. Preoperative embolization of tumor before transoral resection has sometimes been recommended. Also, small lesions can be amenable to laser resection.